Insulin Resistance and Other Comorbidities of Obesity as Independent Variables on Ventricular Repolarization in Children and Adolescents - Ilhan, Zehra; Bekdas, Mervan; Inanir, Mehmet; Kabakus, Nimet (Sudan Journal of Medical Sciences, 2022)
Background: Obesity, a rapidly increasing global health problem in all age groups, is accepted as the basis for many chronic diseases through insulin resistance mechanism. This study aimed to examine whether insulin resistance and other comorbidities of obesity have an effect on the cardiac conduction system. Methods: The study included 50 obese and 47 healthy individuals aged 6–18 years. ECGs of all cases were taken; ECG waves and intervals were measured manually. Results: Of the obese group, 19 were boys (38%) and 31 were girls (62%), 27 were children (54%) and 23 were adolescents (46%), their ages were 11.3 ± 3.5 years. These particular characteristics were similar compared to the control group. However, in the obese group, the ECG parameters QTc (p = 0.001), QTd (p < 0.001), QTdc (p < 0.001), JTc (p < 0.001), Tp-e (p < 0.001), Tp-e/QT (p < 0.001), Tp-e/QTc (p < 0.001), Tp-e/JT (p < 0.001), and Tp-e/JTc (p < 0.001) were significantly longer. Twenty-five obese subjects (50%) had insulin resistance, when ECG parameters are compared to those without it, only JTc was significantly longer (332.3 ± 16.5 vs 321.7 ± 17.7 ms, p = 0.033). JTc duration mostly affected JT (p < 0.001) and QTc (p < 0.001). The 327 ms cut-off value of JTc indicated insulin resistance in the obese patients (p = 0.044) (sensitivity 60%, specificity 60%). Conclusion: Insulin resistance and other comorbidities of obesity may cause ventricular repolarization abnormalities at an early age. JTc, an ECG parameter, can be a guide in assessing ventricular repolarization abnormality and the risk of arrhythmia in these patients. Keywords: obesity, insulin resistance, comorbidities, ventricular repolarization, child, adolescence